Quantification of PAHs and oxy-PAHs on airborne particulate matter in Chiang Mai, Thailand, using gas chromatography high resolution mass spectrometry - Walgraeve,C. (Pergamon Press Ltd., 2015)
© 2015 Elsevier Ltd. An analytical method using gas chromatography high resolution mass spectrometry was developed for the determination of 16 polycyclic aromatic hydrocarbons (PAHs) and 12 oxygenated PAHs (of which 4 diketones, 3 ketones, 4 aldehydes and one anhydride) on atmospheric particulate matter with an aerodynamic diameter less than 10μm (PM10). The magnetic sector mass spectrometer was run in multiple ion detection mode (MID) with a mass resolution above 10000 (10% valley definition) and allows for a selective accurate mass detection of the characteristic ions of the target analytes. Instrumental detection limits between 0.04pg and 1.34pg were obtained for the PAHs, whereas for the oxy-PAHs they ranged between 0.08pg and 2.13pg. Pressurized liquid extraction using dichloromethane was evaluated and excellent recoveries ranging between 87% and 98% for the PAHs and between 74% and 110% for 10 oxy-PAHs were obtained, when the optimum extraction temperature of 150°C was applied. The developed method was finally used to determine PAHs and oxy-PAHs concentration levels from particulate matter samples collected in the wet season at 4 different locations in Chiang Mai, Thailand (n=72). This study brings forward the first concentration levels of oxy-PAHs in Thailand. The median of the sum of the PAHs and oxy-PAHs concentrations was 3.4ng/m3 and 1.1ng/m3 respectively, which shows the importance of the group of the oxy-PAHs as PM10 constituents. High molecular weight PAHs contributed the most to the ∑PAHs. For example, benzo[ghi]perylene was responsible for 30-44% of the ∑PAHs. The highest contribution to ∑oxy-PAHs came from 1,8-napthalic anhydride (26-78%), followed by anthracene-9,10-dione (4-27%) and 7H-benzo[de]anthracene-7-one (6-26%). Indications of the degradation of PAHs and/or formation of oxy-PAHs were observed.